Client experience of food assistance programs among adults in the United States: a qualitative evidence synthesis protocol - Rhodes, Elizabeth C.; Nyhan, Kate; Okoli, Ngozi; O’Connor Duffany, Kathleen; Rodriguez, Maria Elena; Perkins, Benjamin; Ross, Daniel; Pérez-Escamilla, Rafael (Frontiers in Public Health, 2023)
Introduction Policymakers, health practitioners, and other key partners are increasingly focused on ensuring that clients of food assistance programs have positive experiences, a key aspect of high-quality programming. The objectives of this review are to describe the experiences of clients participating in food assistance programs in the United States (US) and to identify ways that these programs promote or hinder positive experiences. Methods and analysis We will conduct a qualitative evidence synthesis with partners from food security organizations and community members. Peer-reviewed literature will be systematically searched in Scopus, CINAHL, and AGRICOLA. To identify grey literature, we will use Google’s programmable search engine. This review will consider sources that present results of primary qualitative studies that focus on at least one food assistance program in the US and explore the perspectives of adult clients. Only sources published in English or Spanish from 2007 onward will be included. Multiple reviewers will screen articles for inclusion and extract data from articles that meet the inclusion criteria, using a structured data extraction tool. Thematic synthesis or meta-ethnography may be appropriate approaches for synthesizing the extracted data. The final selection of synthesis method will be determined once the set of primary qualitative studies to be included in the review is complete and the type of data presented in these studies is known. We will assess the methodological quality of the included studies using the CASP (Critical Appraisal Skills Programme) tool for qualitative studies and assess the confidence in the review findings using the GRADE-CERQual (Confidence in Evidence from Reviews of Qualitative research) approach. Discussion The findings of this review will inform the development of measures to assess client experience and quality improvement efforts.